New insights into trends of rainfall extremes in the Amazon basin through trend‐empirical orthogonal function (1981–2021) - Cerón, Wilmar L.; Kayano, Mary T.; Andreoli, Rita V.; Canchala, Teresita; Avila-Diaz, Alvaro; Ribeiro, Igor O; Rojas, Juan D; Escobar Carbonari, Daniel; Tapasco, Jeimar (Wiley, 2024)
Abstract Studies related to monitoring changes in frequency, intensity and duration of precipitation extremes are key to creating efficient climate change measures and forest conservation policies. This study describes new insights into rainfall precipitation extremes over the Amazon basin (AB) during the last four decades (1981–2021) from the Climate Hazards Group InfraRed Precipitation with Station data (CHIRPSv2). Here we analysed the trends of daily extreme precipitation indices proposed by the Expert Team on Climate Change Detection and Indices (ETCCDI) at the seasonal scale, using the trend‐empirical orthogonal function (TEOF). Our results indicate that the frequency of precipitation extremes increased over Peruvian Amazonia and northeastern Brazilian Amazonia, and reduced in the centre of AB, mainly during the first seasons of the year: December–January–February (DJF) and March–April–May (MAM). The cooling trend over the eastern and central tropical Pacific and the warming trend over the tropical and western subtropical Pacific could associate with the increase in frequency of precipitation extremes in DJF. Furthermore, during June–July–August (JJA) and September–October–November (SON), rainfall intensity indices showed a decrease in Colombia and the Bolivian Amazon; in contrast, northern and southern Peru delivered an increased pattern. The trend pattern in the JJA and SON seasons could be associated with a warming trend over most of the North Atlantic and a cooling in the 40°–60° S band. Our results demonstrate that the precipitation extremes over the AB have spatially varying trends. These heterogeneous trends over the space might be take into account for robust adaptation policies over the countries that are parts of the AB, such as Bolivia, Brazil, Colombia, Ecuador, Guyana, Perú, Surinam and Venezuela.